PENYULUHAN RUMAH SEDERHANA TAHAN GEMPA - Mellisa Fitri Andriyani Muzakir (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Kalisat, Selomirah village, District Ngablak, Magelang, Central Java. DusunKalisat community is very open minded  with changes, so the village has experiencedgood progress in the field of livelihood and education. The geographical location ofMagelang district near merbabu mountain and merpapi mountain make the area in thedistrict are vulnerable to natural disasters. Especially landslides and earthquakes. Weneed a building resistant to earthquakes but not spend a lot of costs, sothat the peopleof Dusun Kalisat have guidance on how to build a house to be resistant to earthquakesbut not spend a lot of cost. To resolve this issue held counseling simple housesearthquake resistant.